DAYA SAING USAHATANI UBIKAYU UNTUK BIOFUEL DI LAHAN KERING KABUPATEN LAMPUNG TENGAH - Abidin, Zainal (Lampung University)
With constant increase of fossil fuel recently, the search for biofuel as alternative source of energy has been increasing recently. Cassava is among agriculture crop that is potential for biofuel production. This study intends to determine the competitiveness of cassava farming for biofuel in Central Lampung District of Lampung. The study employs policy analysis matrix involving 38 farmers who were randomly selected. The study was carried out from mid June to December 2007. The study suggests that thanks to icnrease of cassava price at farm level, the farmers have gained substantial benefits from cassava farming, The study suggests that the cassava farming is very profitable and competitive. It provides net private and social profits of Rp 6,88 millions and Rp 6,72 millions per hectare respectively. Even, if subsidy for urea fertilizer is removed, the farmer is still gaining hefty profits. The farming is also efficient in terms of using domestic resources as shown with the value of domestic resource cost (DRC) at 0,43 with subsidy and 0,44 without subsidy suggesting that this farming needs only 43 to 44 cent to obtain US 1 revenues. Henceforth, this farming is among the likeable choice by farmers in Kabupaten Lampung Tengah.